Uji Skrining Fitokimia Ekstrak Etanol Daun Ubi Jalar Ungu (Ipomoea Batatas L.) - Lidyawati Lidyawati; Sasmiati Farach Dita; Cut Melly Agustiany (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Purple sweet potato leaf (Ipomoea batatas L.) is one of the plants that has begun to be used as a traditional or herbal medicine. This study aims to determine the content of secondary metabolites from purple sweet potato leaves. This research was conducted at the Chemistry Laboratory, Faculty of Tarbiyah, State Islamic University of Ar-Raniry Banda Aceh with laboratory testing methods. Purple sweet potato leaves were extracted by maceration using 5 L 96% ethanol for 5 days and evaporated in a vacuum rotary evaporator to form a thick extract. Furthermore, phytochemical screening tests were carried out. The test results stated that purple sweet potato leaf extract contains Alkaloids (+++), Flavonoids (+), Tannins (+), Saponins (+), Terpenoids (+), and Steroids (+).